Modulation of the Gut Microbiota by Sihocheonggan-Tang Shapes the Immune Responses of Atopic Dermatitis - Chun, Jaemoo; Lee, So Min; Ahn, You Mee; Baek, Min-Gyung; Yi, Hana; Shin, Sarah; Jung, Jeeyoun (Frontiers in Pharmacology, 2021)
Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized by complex immune dysregulation and closely related to the gut microbiome. The present study investigated the microbiome-mediated effect of Sihocheonggan-Tang (SHCGT) on AD-like symptoms induced by 2,4-dinitrochlorobenzene (DNCB) in BALB/c mice. DNCB was applied regularly to the ear and dorsal skin of BALB/c mice, and SHCGT was administered orally daily for 2 weeks. The composition of the gut microbiota was analyzed using 16S rRNA sequencing, and the effect of gut microbiome-derived metabolites, specifically short-chain fatty acids (SCFAs), was evaluated in tumor necrosis factor-alpha (TNF-α)- and interferon-gamma (IFN-γ)-treated HaCaT cells. SHCGT alleviated DNCB-induced symptoms of AD and the immune response to AD by decreasing the plasma immunoglobulin E level and splenic interleukin-4, interleukin-10, TNF-α, and IFN-γ levels. The gut microbiome composition and the damaged gut epithelial barrier in mice with AD were also significantly altered by SHCGT, and the reduced SCFA levels therein were elevated. We found that SFCAs directly inhibited the mRNA expression of IL-6 and ICAM-1 in TNF-α- and INF-γ-treated HaCaT cells. The finding that SHCGT regulates the gut microbiome and improves DNCB-induced AD in mice suggests that this herbal medicine has therapeutic potential in patients with AD.